Allelic Variation in Protein Tyrosine Phosphatase Receptor Type-C in Cattle Influences Erythrocyte, Leukocyte and Humoral Responses to Infestation With the Cattle Tick Rhipicephalus australis - Jonsson, Nicholas N.; Cox, David K.; Piper, Emily K.; Valdivieso, Emily F. Mantilla; Constantinoiu, Constantin; Jackson, Louise A.; Stear, Michael J.; Ross, Elizabeth M.; Tabor, Ala E. (Frontiers in Immunology, 2021)
The protein tyrosine phosphatase receptor type-C (PTPRC) gene encodes the common leukocyte antigen (CD45) receptor. CD45 affects cell adhesion, migration, cytokine signaling, cell development, and activation state. Four families of the gene have been identified in cattle: a taurine group (Family 1), two indicine groups (Families 2 and 4) and an African “taurindicine” group (Family 3). Host resistance in cattle to infestation with ticks is moderately heritable and primarily manifests as prevention of attachment and feeding by larvae. This study was conducted to describe the effects of PTPRC genotype on immune-response phenotypes in cattle that display a variable immune responsiveness to ticks. Thirty tick-naïve Santa-Gertrudis cattle (a stabilized composite of 5/8 taurine and 3/8 indicine) were artificially infested with ticks weekly for 13 weeks and ranked according to their tick counts. Blood samples were taken from control and tick-challenged cattle immediately before, then 21 d after infestation and each subsequent week for 9 weeks. Assays included erythrocyte profiles, white blood cell counts, the percentage of cellular subsets comprising the peripheral blood mononuclear cell (PBMC) population, and the ability of PBMC to recognize and proliferate in response to stimulation with tick antigens in vitro. The cattle were PTPRC genotyped using a RFLP assay that differentiated Family 1 and 3 together (220 bp), from Family 2 (462 bp), and from Family 4 (486 bp). The PTPRC allele frequencies were Family 1/3 = 0.34; Family 2 = 0.47; Family 4 = 0.19. There was no significant association between PTPRC genotype and tick count. Each copy of the Family 1/3 allele significantly decreased total leucocyte count (WCC) and CD8+ cells. Increasing dosage of Family 2 alleles significantly increased red blood cell count (RCC), haematocrit (PCV), and haemoglobin (Hb) concentration in blood. Increasing dosage of the Family 4 allele was associated with increased WCC, reduced RCC, reduced PCV and reduced Hb. Homozygote Family 1/3 animals had consistently lower IgG1 in response to tick Ag than homozygote Family 2 animals. The PTPRC genotype influences the bovine immune response to ticks but was not associated with the observed variation in resistance to tick infestation in this study.